Pengaruh Green Marketing, Eco-Efficiency, dan Investment Knowledge terhadap Keputusan Investasi Berkelanjutan pada Investor Muda - Maharani Alya Az-zahra; Iin Trya Shavira; Derry Muharram Sodikin; M. Lutphi Nessa; Sunita Dasman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study is motivated by the growing trend of ESG-based sustainable investment globally amid a shift in the orientation of young investors. This study aims to analyze the influence of Green Marketing, Eco-Efficiency, and Investment Knowledge on Sustainable Investment Decisions among young investors in Indonesia. A quantitative approach with a survey method was employed involving 100 respondents selected through purposive sampling based on the criteria of being aged 18–30 years, having investment experience, and possessing exposure to sustainable investment or ESG-related information. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The findings indicate that Green Marketing has a positive and significant effect on Sustainable Investment Decisions (β = 0.231; T = 3.067; p = 0.002), Eco-Efficiency has a positive and significant effect (β = 0.329; T = 5.169; p = 0.000), while Investment Knowledge demonstrates the strongest and most significant influence (β = 0.411; T = 5.854; p = 0.000). The structural model demonstrates an R² value of 0.618 and predictive relevance (Q²) of 0.856. These findings confirm that improving green marketing communication, perceptions of corporate environmental efficiency, and investment knowledge simultaneously contribute significantly to sustainable investment decisions among young investors. Strengthening investment literacy and sustainability information transparency is therefore a strategic priority for encouraging greater participation of younger generations in ESG-based investments.